0646 Evaluation of Increased CPAP Compliance After Electronic Learning Video Aimed at Troubleshooting Common CPAP Related Problems. (27th May 2020) - Slota, K A; Wasey, W; Dredla, B K; Castillo, P
Abstract: Introduction: Obstructive sleep apnea(OSA) is a common diagnosis associated with immediate and long-term health consequences. Due to increasing awareness, the demand for treatment with CPAP is increasing. However, CPAP compliance remains a problem, and may be improved by initial patient education targeted at common CPAP problems Methods: A 10 min video depicting common CPAP related problems was created in the Mayo Clinic Florida Simulation Center using standardized patients. Newly diagnosed patients with OSA requiring CPAP were randomized into two arms: (i) the intervention arm was shown the video and received standard of care; or (ii) in the "placebo" or standard of care alone. Our standard of care includes a review of the sleep study, discussion of diagnosis and recommendation for CPAP therapy along with Mayo OSA information packet, followed by compliance visit at 3 months. Compliance is defined as >4 hours of CPAP use per night gathered from machine's SD card. The two groups were compared for statistically significant difference in compliance at 3 months. Results: 47 patients diagnosed between 10/2018-5/2019 were included in the study(21:intervention, 26:placebo). 7 (33%) and 7 (26%) patients in the intervention and the placebo came back for follow up visit (p=0.63). Among them, median CPAP usage was 362.5 min (236.0, 480.0) in intervention arm vs 351.0 min (125.0, 466.0) in placebo group and the difference was not significant. Average nightly use of >than 4 hours was 12(57.1%) in the intervention group and 17(65.4%) in placebo group. Conclusion: In this group addition of an educational video to standard of care did not show benefit in CPAP compliance. There was a tendency toward greater median nightly usage. Patients receiving the video had a higher likelihood of making their follow up appointment which is pivotal, as it provides an opportunity for further intervention and enhancement of adherence. Support: Mayo Clinic Jacksonville